STUDI STABILITAS SISTEM SUB SURFACE FLOW CONSTRUCTED WETLAND (SSF-CW) MENGGUNAKAN TANAMAN MELATI AIR DAN MEDIA TANAM ZEOLIT UNTUK MENURUNKAN LOGAM Hg - Angge Dhevi Warisaura; Ilma Fadlilah; Agus Prasetya; Moh. Fahrurrozi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2019)
Amalgamation to gold in artisanal small scale generally uses mercury (Hg) that decrease the quality of environment especially water. A study of mercury artisanal small scale gold mine waste water was conducted by utilizing simple technology using Sub Surface Flow - Constructed Wetland (SSF-CW) system. This system is a combination of phytoremediation methods using Echinodorus palaefolius plant with zeolite as growth media. The purpose of this study was to determine the stability of SSF-CW in reducing Hg concentration in water. This SSF-CW system model has dimensions of 820 mm x 320 mm x 585 mm consisting of 3 zones, namely the inlet zone, the reaction zone and the outlet zone. The study was conducted with an initial HgCl2 waste concentration of 14.94 mg / L which was carried out in two stages, continuous and batch for 12 hours and lasted for 3 days for each stage. Effluent samples were taken every 0 hours, 4 hours, 8 hours, and 12 hours for mercury concentration analysis using Direct Mercury Analyzer (DMA). The result showed that SSF-CW could support the process of reducing Hg concentration n wastewater with removal efficiency of 98.99%. Echinodorus had the ability to accumulate metals with a BCF value of 9,117 and the accumulation of Hg in the zeolite (as growth media) was still far from the saturated capacity to absorb mercury.